Romeo & Juliet - Shakespeare, William; Edited By Gill, Roma (Oxford Oxford University Press, 2008)
The classic tragedy about the doomed young lovers is accompanied by historical and critical notes.
Include Illustrations
Keywords: Italy--Verona -- Juliet (Fictitious character) -- Youth